Does private tutoring payoff? - Ayfer Gurun; Daniel L. Millimet (Institute for the Study of Labor (IZA), 2008)
We assess the causal effect of private tutoring on the probability of university placement in Turkey. We find that tutoring increases the probability of being placed in a university when non-random selection is ignored. Moreover, among those utilizing private tutoring, greater expenditure on tutoring is also positively associated with university placement. However, we find evidence of positive selection into tutoring, but negative selection into greater expenditures among those receiving tutoring. Accounting for this pattern of non-random selection, we conclude that private tutoring has a negative causal effect on university placement overall, but conditional on receiving any tutoring, spending more on tutoring has a positive causal effect on university placement.
urn:nbn:de:101:1-20080820239
Keywords: C31; 330; Tutoring; Turkey; tertiary education; program evaluation; Privatschule; Studium; Bildungsabschluss; Türkei